Library Services and Right to Information: Exploring Access to Information and User Rights in Library Services (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The primary purpose of the library is to provide the user with information and services in a variety of platforms to meet their desires for education, awareness and personal well-being, such as entertainment and recreational activities. There are many specifics which are restricted to the user. Access to information grants the owner the right to use expertise that may formerly be limited.